Salivary and imaging-based biomarkers of radiation therapy-induced xerostomia - Saira Atif; Norsila Abdul Wahab; Sarah Ghafoor; Muhammad Qasim Saeed; Azlina Ahmad (Journal of the Pakistan Medical Association, 2020)
Abstract Biomarkers are anatomical characteristics or naturally occurring measurable molecules indicating physiological or pathological state of an individual. These biomarkers have the potential to detect or predict diseases at an early stage which is particularly beneficial in timely management of the common complications of radiation therapy done in head and neck cancer treatment regime. Xerostomia is one of the most common oral complaints of radiation therapy. Saliva has an abundance of protein biomarkers; however, those related to post-radiation therapy xerostomia needs to be explored further. Textural and imaging-based biomarkers are helpful in predicting xerostomia in such patients. This narrative review provides an account of the salivary protein and imaging-based biomarkers of radiation therapy-induced xerostomia in head and neck cancer patients. Keywords: chemotherapy, mouth dryness, head and neck cancer, radiotherapy, salivary glands